Genetic and developmental basis for fin shape variation in African cichlid fishes. Issue 1 (30th November 2016) - Navon, Dina; Olearczyk, Nathan; Albertson, R. Craig
Abstract: Adaptive radiations are often characterized by the rapid evolution of traits associated with divergent feeding modes. For example, the evolutionary history of African cichlids is marked by repeated and coordinated shifts in skull, trophic, fin and body shape. Here, we seek to explore the molecular basis for fin shape variation in Lake Malawi cichlids. We first described variation within an F2 mapping population derived by crossing two cichlid species with divergent morphologies including fin shape. We then used this population to genetically map loci that influence variation in this trait. We found that the genotype–phenotype map for fin shape is largely distinct from other morphological characters including body and craniofacial shape. These data suggest that key aspects of fin, body and jaw shape are genetically modular and that the coordinated evolution of these traits in cichlids is more likely due to common selective pressures than to pleiotropy or linkage. We next combined genetic mapping data with population‐level genome scans to identify wnt7aa and col1a1 as candidate genes underlying variation in the number of pectoral fin ray elements. Gene expression patterns across species with different fin morphologies and small molecule manipulation of the Wnt pathway during fin development further support the hypothesis that variation at these loci underlies divergence in fin shape between cichlid species. In all, our data provide additional insights into the genetic and molecular mechanisms associated with morphological divergence in this important adaptive radiation.